Correction: Long-Term Low Carbohydrate Diet Leads to Deleterious Metabolic Manifestations in Diabetic Mice. - Keiko Handa; Kouichi Inukai; Hirohisa Onuma; Akihiko Kudo; Fumiyuki Nakagawa; Kazue Tsugawa; Atsuko Kitahara; Rie Moriya; Kazuto Takahashi; Yoshikazu Sumitani; Toshio Hosaka; Hayato Kawakami; et al. (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0104948.].